Nasaid na yaman. - Papag, Ron M.; Padilla, Amwerina V.; Felicia, R.E; Guzman. Ros-B; Oliveros, Reynaldo; Velasco, Federico N.; Eroa, Luther Jose O. (AV036., 1998)
Describes the state of the Philippine environment and explains in detail why it has reached the critical point.